Spectral properties and factors determining high quantum yield of thioflavin T incorporated in amyloid fibrils. Issue 1 (2010) - Sulatskaya, A. I.; Turoverov, K. K.; Kuznetsova, I. M.
Abstract : Benzthiazole dye thioflavin T (ThT) is widely used for studying amyloid fibrils structure and formation. Nevertheless, till now there is no common opinion concerning molecular mechanisms of ThT binding to amyloid fibrils and the reasons of dramatic increase of its fluorescence quantum yield on incorporation into amyloid fibrils. Our data prove that ThT molecules incorporate in amyloid fibrils in monomeric form and there is no ground to suppose the formation of ThT dimers, eximers, or micelles. It was shown that the increase of quantum yield of ThT incorporated in amyloid fibrils is caused by restriction of benzthiazole and aminobenzene rings torsion fluctuations about each other.